Bioinspired mp20 mimicking uricase in ZIF-8: metal ion dependent for controllable activity - Abdul Aziz, Siti Fatimah Nur; Salleh, Abu Bakar; Normi, Yahaya M.; Mohammad Latif, Muhammad Alif; Alang Ahmad, Shahrul Ainliah (Elsevier, 2024)
Mini protein mimicking uricase (mp20) has shown significant potential as a replacement for natural enzymes in the development of uric acid biosensors. However, the design of mp20 has resulted to an inactive form of peptide, causing of loss their catalytic activity. Herein, this paper delineates the impact of various metal cofactors on the catalytic activity of mp20. The metal ion-binding site prediction and docking (MIB) web server was employed to identify the metal ion binding sites and their affinities towards mp20 residues. Among the tested metal ions, Cu2+ displayed the highest docking score, indicating its preference for interaction with Thr16 and Asp17 residues of mp20. To assess the catalytic activity of mp20 in the presence of metal ions, uric acid assays was monitored using a colorimetric method. The presence of Cu2+ in the assays promotes the activation of mp20, resulting in a color change based on quinoid production. Furthermore, the encapsulation of the mp20 within zeolitic imidazolate framework-8 (ZIF-8) notably improved the stability of the biomolecule. In comparison to the naked mp20, the encapsulated ZIFs biocomposite (mp20@ZIF-8) demonstrates superior stability, selectivity and sensitivity. ZIF's porous shells provides excellent protection, broad detection (3–100 μM) with a low limit (4.4 μM), and optimal function across pH (3.4–11.4) and temperature (20–100°C) ranges. Cost-effective and stable mp20@ZIF-8 surpasses native uricase, marking a significant biosensor technology breakthrough. This integration of metal cofactor optimization and robust encapsulation sets new standards for biosensing applications.